MODUL PEMBELAJARAN FISIKA MATERI SUHU DAN KALOR BERBASIS MODEL INKUIRI TERBIMBING UNTUK KELAS X SMA (Jurnal Luminous: Riset Ilmiah Pendidikan Fisika, 2022)
The research objectives of the Physics learning module based guided inquiry models on the material ofÂ  Suhu dan Kalor (Temperature and Heat)for class X SMA: (1) knowing the characteristics of the physics module based guide inquiry on the material of suhu dan kalor (temperature and heat); (2) testing the feasibility of the Physics module based on guided inquiry at the material of suhu dan kalor (temperature and heat). The design of this research is ADDIE development wich is developed by Dick and Carry (1996), which includes: AnalyzeÂ  (Analisis), Design (Design), Develop (Development), Implemen (Application), and Evaluate (Evaluation). The research instrument uses a feasibility questionnaire sheet. Data analysis was carried out by means of a feasibility test by the learning experts. Based on the data analysis, the results showed: (1) Physisc module products based on the guided inquiry were developed based on guided inquiry activities, based on the assesment of the instructional experts on the characteristics of guided inquiry modules in the â€œvery feasibelâ€ category with a percentage of eligibility of 92,6%; (2) the feasibility of the Physics module based guide inquiry on the material of suhu dan kalor(temperature and heat), it is based on the assessment of learning experts in the category of â€œvery feasibelâ€ with the percentage of feasibility of 91,6%; (3) The practicilaty of physice module based guide inquiry on the material of suhu dan kalor (temperatire and heat) based on the assesment of class X Students of SMA PAB 4 Sampali in the â€œvery practicalâ€œ category with apa feasibility percent of 90,3%. So, it can be concluded that the Physics learning module based on the guided inquiry model is very valid to be used in the learning process.